APPLICATION OF REMOTE SENSING AND GIS TECHNOLOGIES TO RESEARCHING SHORELINE FLUCTUATION PROCESS AND INLET OPENING/CLOSING IN O LOAN LAGOON (PHU YEN) FROM 1965 TO 2014 - Binh, Tran Van; Son, Tong Phuoc Hoang; Dan, Nguyen Dinh; Trung, Pham Ba (Vietnam Journal of Marine Science and Technology, 2015)
Application of remote sensing and GIS (Geographic Information System) technologies found that: Fluctuation process of shoreline in O Loan lagoon became evident, through which a general picture of the shoreline development in a long time from 1965 - 2014 has been launched. The process of erosion - accretion evolutions occurred time by time. In which, the period from 1965 - 1995 was the process of erosion - accretion and gradual northward movement of O Loan lagoon inlet, with erosion area greater than deposition area. The period after 1995 was the process of erosion and An Hai inlet opening during rainy season, coincident with northeast monsoon and typhoon activity; and the process of accretion and An Hai inlet closing during dry season, coincident with southwest monsoon.